Targeting DDR2 in head and neck squamous cell carcinoma with dasatinib - Mäßenhausen, Anne Friederike von; Sanders, Christine; Brägelmann, Johannes; Konantz, Martina; Queisser, Angela; Vogel, Wenzel; Kristiansen, Glen; Duensing, Stefan; Schröck, Andreas; Bootz, Friedrich; Brossart, Peter; Kirfel, Jutta; et al. (International journal of cancer, 2016)
Squamous cell carcinoma of the head and neck (HNSCC) is the tenth most common tumor entity in men worldwide. Nevertheless therapeutic options are mostly limited to surgery and radio-chemotherapy resulting in 5-year survival rates of around 50%. Therefore new therapeutic options are urgently needed. During the last years, targeting of receptor tyrosine kinases has emerged as a promising strategy that can complement standard therapeutical approaches. Here, we aimed at investigating if the receptor tyrosine kinase DDR2 is a targetable structure in HNSCC. DDR2 expression was assessed on a large HNSCC cohort (554 patients) including primary tumors, lymph node metastases and recurrences and normal mucosa as control. Subsequently, DDR2 was stably overexpressed in two different cell lines (FaDu and HSC-3) using lentiviral technology. Different tumorigenic properties such as proliferation, migration, invasion, adhesion and anchorage independent growth were assessed with and without dasatinib treatment using in-vitro cell models and in-vivo zebrafish xenografts. DDR2 was overexpressed in all tumor tissues when compared to normal mucosa. DDR2 overexpression led to increased migration, invasion, adhesion and anchorage independent growth whereas proliferation remained unaltered. Upon dasatinib treatment migration, invasion and adhesion could be inhibited in-vitro and in-vivo whereas proliferation was unchanged. Our data suggest treatment with dasatinib as a promising new therapeutic option for patients suffering from DDR2 overexpressing HNSCC. Since dasatinib is already FDA-approved we propose to test this drug in clinical trials so that patients could directly benefit from this new treatment option.
Gesehen am 04.06.2020